2006
DOI: 10.1074/jbc.m510171200
|View full text |Cite
|
Sign up to set email alerts
|

The Carbohydrate at FcγRIIIa Asn-162

Abstract: FcgammaRIIIa plays a prominent role in the elimination of tumor cells by antibody-based cancer therapies. Non-fucosylated bisected IgGs bind this receptor with increased affinity and trigger FcgammaRIII-mediated effector functions more efficiently than native, fucosylated antibodies. In this study the contribution of the carbohydrates of both binding partners to the strength of the complex was analyzed. Glycoengineering of the antibody increased affinity for two polymorphic forms of soluble human FcgammaRIIIa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 317 publications
(113 citation statements)
references
References 29 publications
4
109
0
Order By: Relevance
“…, 19 Between the two variants, FcγRIIIa-V158 has a higher affinity to human IgG1. For example, under similar experimental conditions, FcγRIIIa-V158 demonstrated an approximately 10-fold higher affinity for IgG than FcγRIIIa-F158 20 . Cells expressing the FcγRIIIa-V158 allele mediate ADCC more effectively 19 .…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…, 19 Between the two variants, FcγRIIIa-V158 has a higher affinity to human IgG1. For example, under similar experimental conditions, FcγRIIIa-V158 demonstrated an approximately 10-fold higher affinity for IgG than FcγRIIIa-F158 20 . Cells expressing the FcγRIIIa-V158 allele mediate ADCC more effectively 19 .…”
Section: Introductionmentioning
confidence: 94%
“…Nonetheless, the authors did highlight that Asn162 is a potential glycosylation site of FcγRIII that is close to a binding site and a larger carbohydrate moiety attached to this site may influence the affinity to IgG 9 . Indeed, a subsequent study revealed that, compared to the unglycosylated form of FcγRIII (by mutating Asn162 to Gln162), the glycosylated FcγRIII (Asn162) showed reduced affinity for native (fucosylated) IgG antibodies, while antibodies with or without the core fucose showed a similar affinity for unglycosylated FcγRIII 20 . However, when fucose-free antibody binds glycosylated FcγRIII (Asn162), the affinity increased significantly.…”
Section: Molecular Mechanisms To Account For the Enhanced Affinity Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…[40][41][42] The binding of the Fc region of antibodies to FcγRIIIa is dependent on interactions between the carbohydrate moieties of both the FcγRIIIa and antibody. 43 Notably, ADCC activity does not differ between Type I and Type II anti-CD20 antibodies, 3 but antibodies such as GA101 have been engineered for enhanced affinity for FcγRIIIa leading to an increased ability to bind and recruit effector cells and hence a higher ADCC level. 27,44 The contribution of ADCC to the clinical activity of antibodies remains to be established.…”
Section: Type I Cd20 Antibodiesmentioning
confidence: 99%